2017
DOI: 10.1152/japplphysiol.00323.2017
|View full text |Cite
|
Sign up to set email alerts
|

Different gene response to mechanical loading during early and late phases of rat Achilles tendon healing

Abstract: Mechanical loading stimulates tendon healing both when applied in the inflammatory phase and in the early remodeling phase of the process, although not necessarily via the same mechanisms. We investigated the gene response to mechanical loading in these two phases of tendon healing. The right Achilles tendon in rats was transected, and the hindlimbs were unloaded by tail suspension. The rats were exposed to 5 min of treadmill running 3 or 14 days after tendon transection. Thereafter, they were resuspended for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…This might explain the tendency to stronger tendons in fully loaded contaminated rats compared to the clean (p = 0.056). The early callus is dominated by different leukocytes, and the composition of these cells undergoes dramatic change during the early healing phases in our model [8][9][10]. Full loading, in contrast to partial unloading, can result in tissue microdamage followed by a pro-inflammatory response [7].…”
Section: Plos Onementioning
confidence: 94%
See 2 more Smart Citations
“…This might explain the tendency to stronger tendons in fully loaded contaminated rats compared to the clean (p = 0.056). The early callus is dominated by different leukocytes, and the composition of these cells undergoes dramatic change during the early healing phases in our model [8][9][10]. Full loading, in contrast to partial unloading, can result in tissue microdamage followed by a pro-inflammatory response [7].…”
Section: Plos Onementioning
confidence: 94%
“…The magnitude of loading appears to activate different mechanisms which will ultimately lead to different effects on the mechanical properties [7]. The Achilles tendon heals through callus formation and the initial tissue contains weak matrix with primarily leukocytes infiltrating this matrix [8]. Full loading, when applied to this matrix, has been shown to induce microdamage and alter the immune cell composition and ultimately promote a pro-inflammatory response [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the outcome of loading at different phases of healing was the same, different mechanisms could be involved. In the same tendon healing model, it was shown that mechanical loading regulates inflammation-related genes during the inflammatory phase of tendon healing [2][3][4] . However, the possible influence of mechanical loading on magnitude and polarization of immune cells during the course of tendon healing needs to be further investigated.…”
Section: Mechanical Loadingmentioning
confidence: 99%
“…Ruptured tendons heal slowly, and management of tendon injuries is challenging. Mechanical loading improves healing of tendons and has been shown to modulate inflammation-related genes, which points to the important role of inflammation during tendon healing [2][3][4] . There are other factors affecting tendon healing, like nonsteroidal anti-inflammatory drugs (NSAIDs) and corticosteroids.…”
Section: Introductionmentioning
confidence: 99%